Analisis Kebiasaan Guru Dalam Menyusun Rencana Pelaksanaan Pembelajaran di Sekolah Dasar Negeri - Sumartini, Tingtin; Taopik, Deden; Widhiyanti, Windhi; Muslihin, Heri Yusuf; Jaelani, Rusani (Universitas Sebelas Maret, 2024)
This research is based on the fact that many teachers in learning activities still use lesson plans/teaching modules downloaded from the internet or purchased from third parties. This research aims to determine teachers' habits in making RPP/MA from 19 schools in the West Java region. This research uses descriptive qualitative methods. Data was generated from interviews and surveys with data analysis techniques using data reduction, data presentation, drawing conclusions. Based on research results, teachers' habits in compiling lesson plans are mostly downloaded from the internet. The notes resulting from data analysis are as follows: of the 19 samples of lesson plans resulting from making your own as many as 2 samples (10%) and lesson plans resulting from downloading from the internet as many as 17 samples (90%), with the reason that 35% do not have time, 6% have too many tasks. teachers and 59% downloaded the RPP which they felt was practical. The conclusion from the research is that most teachers download lesson plans from the internet for practical and time-effective reasons, then modify them according to school conditions.